Maxillary osteoradionecrosis – review of published literature: incidence, classification, risk factors, physiopathology and prevention (Revista da Faculdade de Odontologia - UPF, 2013)
Introduction: osteoradionecrosis (ORN) of facial bones is a serious complication of radiotherapy. Objective: this literature review was performed to study maxillary osteoradionecrosis, its incidence, classification, risk factors, physiopathology, prevention, and current treatment. Literature review: literature search using Medline was performed for all relevant articles with specific keywords from January 2000 to November 2011 aiming to find current data available on ORN and the paradigm change in physiopathology and prevention of the disease. The literature reviewed showed lack of either controlled or randomized trials, a few prospective studies, and a great amount of retrospective studies. Final considerations: adjunctive hyperbaric oxygen (HBO) therapy may be applied for osteoradionecrosis prevention, before and after dental procedures, with satisfying results. Nonetheless, several studies indicated that HBO therapy is not beneficial.